Studi Islam untuk Kemanusiaan: Pendekatan Sosiologis - Miftahuddin, M (SHAHIH: Journal of Islamicate Multidisciplinary, 2020)
Mainstream Islamic studies in the past generally emphasized normative theological approaches that were theocentric so that there were sides of humanity that were missed, even likely to beconsidered 'against' the sacredness of the text. That's why an anthropocentric approach is important to draw into the mainstream. One of the most important approaches is the sociological approach.  The purpose of this research is to reveal new approaches in Islamic studies mainly using sociological approaches. The methodology used in this article uses descriptive analysis(historical)using library studies as the main source of discussion. The results of this study show that the model of sociological Islamic studies that focuses on the interaction of religion (Islam) and society is important to develop. This is a new tradition of Islamic studies that further upholds the dignity of human being. The implications of these findings may presenta new way in Islamic studies especially on two main things at once: (1) reconstructing Islamicsciences; and (2) building social and humanities basedon Islamic epistemology.